Response of a salt marsh microbial community to metal contamination - Mucha, Ana P.; Teixeira, Catarina; Reis, Izabela; Magalhães, Catarina; Bordalo, Adriano A.; Almeida, C. Marisa R. (Estuarine, coastal and shelf science, 2013)
Salt marshes are important sinks for contaminants, namely metals that tend to accumulate around plant roots and could eventually be taken up in a process known as phytoremediation. On the other hand, microbial communities display important roles in the salt marsh ecosystems, such as recycling of nutrients and/or degradation of organic contaminants. Thus, plants can benefit from the microbial activity in the phytoremediation process. Nevertheless, above certain levels, metals are known to be toxic to microorganisms, fact that can eventually compromise their ecological functions. In this vein, the aim of present study was to investigate, in the laboratory, the effect of selected metals (Cd, Cu and Pb) on the microbial communities associated to the roots of two salt marsh plants. Sediments colonized by Juncus maritimus and Phragmites australis were collected in the River Lima estuary (NW Portugal), and spiked with each of the metals at three different Effects Range-Median (ERM) concentrations (1, 10×, 50×), being ERM the sediment quality guideline that indicates the concentration above which adverse biological effects may frequently occur. Spiked sediments were incubated with a nutritive saline solution, being left in the dark under constant agitation for 7 days. The results showed that, despite the initial sediments colonized by J. maritimus and P. australis displayed significant (p < 0.05) differences in terms of microbial community structure (evaluated by ARISA), they presented similar microbial abundances (estimated by DAPI). Also, in terms of microbial abundance, both sediments showed a similar response to metal addition, with a decrease in number of cells only observed for the higher addition of Cu. Nevertheless, both Cu and Pb, at intermediate metals levels promote a shift in the microbial community structure, with possibly effect on the ecological function of these microbial communities in salt marshes. These changes may affect plants phytoremediation potential and further work on this subject is in need.